Perirenal Fat: A Unique Fat Pad and Potential Target for Cardiovascular Disease. (August 2019) - Liu, Bo-Xun; Sun, Wei; Kong, Xiang-Qing
Although visceral obesity is recognized as a risk factor for cardiovascular diseases (CVDs), the efficacy of omental fat removal in CVD treatment is still controversial. There is a need to identify other visceral fat depots for CVD management. This review aims to provide a summary on perirenal fat as an important risk factor for CVD. Studies on epidemiology, anatomy, and function of perirenal fat were reviewed. Observational studies in humans suggest that excessive perirenal fat increases the risk of hypertension and coronary heart disease. Anatomy studies prove that perirenal fat is unique compared to other connective tissues in that it is well vascularized, innervated, and drains into the lymphatic system. Other special morphological features include a complete fascia border, sympathetic-independent development of architecture, and proximity to the kidneys. Based on these anatomical features, perirenal fat regulates the cardiovascular system presumably via neural reflex, adipokine secretion, and fat–kidney interaction. These new insights suggest that perirenal fat may constitute a promising target for CVD management.